INTERNATIONAL PERSPECTIVES ON CITIZENSHIP EDUCATION: NETNOGRAPHY ON DIGITAL-BASED LEARNING - Haryo Budi Rahmadi; Andrea Abdul Rahman Azzqy (Universitas Budi Luhur, 2025)
Abstract: The ever-evolving global dynamics demand Citizenship Education (PKn) to adapt to increasingly complex cross-border challenges such as climate change, economic disparities, human rights violations, and authoritarianism. This study aims to analyze the key elements of these global issues and their impact on the curriculum and approach of PKn. A descriptive-analytic method based on netnography was employed to gather data from various online references, including social media and Google search trends. Google Trends was utilized to identify current trends, highlighting the relevance of global citizenship issues and the importance of information technology in PKn learning. The findings show that topics such as climate change, economic disparities, and human rights violations dominate searches related to global citizenship issues. The study also emphasizes the need for cross-sector collaboration and updated references to make the PKn curriculum more adaptive to changing times. Results suggest that integrating civic affairs as a dominant element in the curriculum and using information technology can create a more adaptive, relevant, and responsive PKn education in the face of global developments. By identifying and analyzing these global trends, it is hoped that PKn education can help shape a generation that is more aware and responsive to global challenges while building a curriculum that is responsive and relevant to the dynamics of the times. In conclusion, PKn education based on understanding global issues and cross-sector collaboration can help create new citizens who are aware of their social responsibilities in the global world. Abstrak: Dinamika global yang terus berkembang menuntut Pendidikan Kewarganegaraan (PKn) untuk beradaptasi dengan tantangan lintas batas yang semakin kompleks seperti perubahan iklim, kesenjangan ekonomi, pelanggaran HAM, dan otoritarianisme. Penelitian ini bertujuan untuk menganalisis unsur-unsur kunci dari isu-isu global ini dan dampaknya terhadap kurikulum dan pendekatan PKn. Metode deskriptif-analitik berdasarkan netnografi digunakan untuk mengumpulkan data dari berbagai referensi online, termasuk media sosial dan tren pencarian Google. Google Trends digunakan untuk mengidentifikasi tren terkini, menyoroti relevansi isu kewarganegaraan global dan pentingnya teknologi informasi dalam pembelajaran PKn. Temuan menunjukkan bahwa topik-topik seperti perubahan iklim, kesenjangan ekonomi, dan pelanggaran hak asasi manusia mendominasi pencarian terkait masalah kewarganegaraan global. Studi ini juga menekankan perlunya kolaborasi lintas sektor dan referensi yang diperbarui untuk membuat kurikulum PKn lebih adaptif terhadap perubahan zaman. Hasil penelitian menunjukkan bahwa mengintegrasikan urusan kewarganegaraan sebagai elemen dominan dalam kurikulum dan menggunakan teknologi informasi dapat menciptakan pendidikan PKn yang lebih adaptif, relevan, dan responsif dalam menghadapi perkembangan global. Dengan mengidentifikasi dan menganalisis tren global tersebut, diharapkan pendidikan PKn dapat membantu membentuk generasi yang lebih sadar dan responsif terhadap tantangan global sekaligus membangun kurikulum yang responsif dan relevan dengan dinamika zaman. Kesimpulannya, pendidikan PKn berbasis pemahaman isu global dan kolaborasi lintas sektor dapat membantu menciptakan warga negara baru yang sadar akan tanggung jawab sosialnya di dunia global.